Is independence really an opportunity? The experience of entrepreneur-mothers. Issue 2 (22nd February 2018) - Foley, Meraiah; Baird, Marian; Cooper, Rae; Williamson, Sue
Abstract : Purpose: The purpose of this paper is to explore how entrepreneur-mothers experience independence in the transition to entrepreneurship, and whether they perceive independence as an agentic, opportunity-maximisation motive or a constrained, necessity-driven response. Design/methodology/approach: Adopting a qualitative and interpretive approach, the authors analysed interviews with 60 entrepreneur-mothers to refine conceptual understanding of independence. Findings: The authors find that entrepreneur-mothers experience independence not as an opportunity, but as a functional necessity in managing the temporal and perceived moral demands of motherhood. The authors assert that there is a fundamental difference between wanting independence to pursue a more autonomous lifestyle, and needing independence to attend to family obligations, a difference that is not adequately captured in the existing conceptualisation of independence. Consequently, the authors propose the classification of "family-driven entrepreneurship" to capture the social and institutional factors that may disproportionately push women with caregiving responsibilities towards self-employment. Practical implications: This paper proposes that a new category of entrepreneurial motivation be recognised to better account for the social and institutional factors affecting women's entrepreneurship, enabling policymakers to more accurately position and support entrepreneur-mothers. Social implications: The authors challenge the existing framing of independence as an agentic opportunity-seeking motive, and seek to incorporate family dynamics into existing entrepreneurial models. Originality/value: This paper delivers much-needed conceptual refinement of independence as a motivator to entrepreneurship by examining the experiences of entrepreneur-mothers, and proposes a new motivational classification, that of family-driven entrepreneurship to capture the elements of agency and constraint embedded in this transition.